Relaxin ligand/receptor systems in the developing teleost fish brain: Conserved features with mammals and a platform to address neuropeptide system functions - Blasiak, Anna; Gugula, Anna; Gundlach, Andrew L.; Olucha-Bordonau, Francisco E.; Aniello, Francesco; Donizetti, Aldo (Frontiers in Molecular Neuroscience, 2022)
The relaxins (RLNs) are a group of peptide hormone/neuromodulators that can regulate a wide range of physiological processes ranging from reproduction to brain function. All the family members have originated from a RLN3-like ancestor via different rounds of whole genome and gene specific duplications during vertebrate evolution. In mammals, including human, the divergence of the different family members and the emergence of new members led to the acquisition of specific functions for the various relaxin family peptide and associated receptor genes. In particular, in mammals, it was shown, that the role of RLN3 is correlated to the modulation of arousal, stress responses, emotion, social recognition, and other brain functions, positioning this gene/peptide as a potential therapeutic target for neuropsychiatric disorders. This review highlights the evolutionary conservation of relaxin family peptide and receptor gene expression and their associated brain neural circuits. In the zebrafish, the expression pattern of the different relaxin family members has specific features that are conserved in higher species, including a likely similar functional role for the ancestral RLN3-like gene. The use of different model organisms, particularly the zebrafish, to explore the diversification and conservation of relaxin family ligands and receptor systems, provides a relatively high-throughput platform to identify their specific conserved or differential neuromodulatory roles in higher species including human.